Effects of circle-the-sage strategy on secondary schools students' numerical ability in physics in Nigeria - Ukoh, Edidiong Enyeneokpon; Aladejana, Alaba Lawrence (Universitas PGRI Kanjuruhan Malang, 2022)
The study examined effect of circle the sage instructional strategy on students’ numerical ability in Physics in senior secondary schools in Ikere local government of area of Ekiti state. A sample of sixty (60) students was selected for the study. A self-structured Physics Numerical Ability Test was used for data collection. A pre-test post-test quasi experimental research design was employed for the study. Two secondary schools in Ekiti state were chosen for the study. A test-retest method was employed to ascertain the reliability of the instrument, using Pearson Product Moment Correlation (PPMC). Three (3) hypotheses were formulated for the study. Self constructed twenty items multiple choice questions was used to collect the date and the data collected were analysed using ANCOVA. The findings of the study revealed that there was no significant effect of treatment on numerical ability of students in Physics, there was no significant effect of gender on numerical ability of students in Physics and there was no significant interaction effect of treatment and gender on numerical ability of students in Physics. Therefore, the study recommended that, though there was no effect of circle the sage strategiy on students’ numerical ability but cicle the sage with other strategies should be used to teach Physics at all level and be incorporated into the teaching of Physics at the secondary school level.